Best Distribution Selection in Modeling the Interest Rate as a Random Modifier - Fajry Ayu Kusumawati; Agung Prabowo; Agustini Tripena Br. SB; Grida Saktian Laksito (International Journal of Quantitative Research and Modeling, 2024)
The interest rate is seen as a random variable because the interest rate has an unpredictable nature or changes over time. This means that the interest rate cannot be anticipated in the future with a certain degree of certainty. Therefore, mathematical models are needed to predict the behavior and value of future interest rates. The models used in this study were interest rate, uniform distribution , and lognormal distribution. The data used in the study were interest rate data for 2014-2015 and sample data for uniform distribution. The resulting model in interest rate modeling as a random variable uses for uniform and lognormal distributions with the application of data and . The interest rate model as a uniformly distributed random variable is considered better with a smaller standard deviation, , and values compared to the lognormal distribution based on the data used.